2016
DOI: 10.1128/jb.00757-15
|View full text |Cite
|
Sign up to set email alerts
|

NqrM (DUF539) Protein Is Required for Maturation of Bacterial Na + -Translocating NADH:Quinone Oxidoreductase

Abstract: Na؉ -translocating NADH:quinone oxidoreductase (Na ؉ -NQR) catalyzes electron transfer from NADH to ubiquinone in the bacterial respiratory chain, coupled with Na ؉ translocation across the membrane. Na ؉ -NQR maturation involves covalent attachment of flavin mononucleotide (FMN) residues, catalyzed by flavin transferase encoded by the nqr-associated apbE gene. Analysis of complete bacterial genomes has revealed another putative gene (duf539, here renamed nqrM) that usually follows the apbE gene and is present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…The primary transporters NQR and Complex I were studied, as well as the secondary antiporters Mrp, NhaB, and NhaP. The loss of the NQR did not affect growth under challenging sodium and pH conditions, which confirms a recent study by Raba et al [37] who suggested that in contrast to NQR in other species, such as Vibrio [3,23,27,51], Pa-NQR is a proton pump with no affinity for sodium. In addition to that, our results suggest that loss of NQR does not affect pH homeostasis, biofilm formation, or swarming motility, which might be due to complementary proton pumping activity of Complex I.…”
Section: Discussionsupporting
confidence: 73%
“…The primary transporters NQR and Complex I were studied, as well as the secondary antiporters Mrp, NhaB, and NhaP. The loss of the NQR did not affect growth under challenging sodium and pH conditions, which confirms a recent study by Raba et al [37] who suggested that in contrast to NQR in other species, such as Vibrio [3,23,27,51], Pa-NQR is a proton pump with no affinity for sodium. In addition to that, our results suggest that loss of NQR does not affect pH homeostasis, biofilm formation, or swarming motility, which might be due to complementary proton pumping activity of Complex I.…”
Section: Discussionsupporting
confidence: 73%
“…It is necessary for NQR maturation, since the FMNs are required for the transfer of the electrons through the NQR complex. NqrM was predicted to deliver Fe to subunits NqrD and NqrE ( Kostyrko et al, 2015 ). Subunits NqrD and NqrE harbor an iron cluster located in the midst of the membrane part of NQR which is proposed to participate in intramolecular electron transfer ( Steuber et al, 2014b ).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the data with PEG-2 and PEG-2S support this agent as an effective inhibitor of Na + -NQR. The experiments with subbacterial membrane vesicles allowed the measurement of Na + -NQR activity directly when the enzyme was operating in a physiologically relevant background (being placed in its native membrane and supplying electrons taken from NADH to the respiratory chain) but without additional permeability barriers and influences from cytoplasmic metabolism (Bertsova and Bogachev 2004;Fadeeva et al 2007Fadeeva et al , 2008; Kostyrko et al 2016). In this model, PEG-2S exhibited a low MIC 50 of 1.76 nmol/L (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Na + -NQR activity can be differentially measured in sub-bacterial membrane vesicles as the NQR-mediated oxidation of an NADH analog, dNADH (Bertsova and Bogachev 2004;Fadeeva et al 2007Fadeeva et al , 2008; Kostyrko et al 2016). This allows the measurement of NQR activity directly without confounding factors -the enzyme is functioning in its native membrane and feeding the electrons taken from NADH to the respiratory chain.…”
Section: Direct Measurement Of Inhibition Of Na + -Nqr By Peg-2smentioning
confidence: 99%